2012
DOI: 10.1167/iovs.11-8958
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Clinical Macular Changes and Retinal Function in Age-Related Macular Degeneration

Abstract: Steady state thresholds (F14Hz and BCT) and clinical signs showed significant concordance across the spectrum of early AMD fundus changes. This suggests that these tests may be an effective tool for monitoring progression of AMD to supplement clinical grading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 40 publications
5
62
0
Order By: Relevance
“…However, we did not always find a reduction in sensitivity when clinical fundus signs, such as the addition of pigmentary disturbance or in the presence of GA, were seen in the fellow eye, indicating a higher clinical risk for progression. Consistent with our earlier reports using other functional modalities, 14 we found that the group with drusen 63 to 125 lm in size had most variation in sensitivity in the inner rings, in both test modalities, suggesting that at this stage of AMD some people will have normal function while others will have quite abnormal results. Perhaps at this stage we might be able to differentiate those destined to have progression and those less likely to do so.…”
Section: Discussionsupporting
confidence: 91%
“…However, we did not always find a reduction in sensitivity when clinical fundus signs, such as the addition of pigmentary disturbance or in the presence of GA, were seen in the fellow eye, indicating a higher clinical risk for progression. Consistent with our earlier reports using other functional modalities, 14 we found that the group with drusen 63 to 125 lm in size had most variation in sensitivity in the inner rings, in both test modalities, suggesting that at this stage of AMD some people will have normal function while others will have quite abnormal results. Perhaps at this stage we might be able to differentiate those destined to have progression and those less likely to do so.…”
Section: Discussionsupporting
confidence: 91%
“…5, 14, 46, 49 Further investigation of this issue is merited, especially in light of a recent study suggesting that 14 Hz flicker and blue color thresholds have good diagnostic sensitivity and ease of test administration. 20 Rod-mediated dark adaptation was assessed in one eye only, unlike the other visual function tests measured in both eyes; however, even with the reduced sample size, there was adequate statistical power to demonstrate significant differences in rod-intercept between the two groups. In addition, the pattern of results was unchanged when analyses were restricted to eyes for which dark adaptation was measured.…”
Section: Discussionmentioning
confidence: 99%
“…These include spatial contrast sensitivity, visual acuity under low luminance and/or low contrast, photopic and scotopic light sensitivity, flicker sensitivity, and dark adaptation. 4–20 The purpose of this study was to assess several visual functional measures in eyes in normal macular health and eyes in the very earliest stages of AMD. Our goal is to understand which aspects of visual function are significantly impacted in the initial stages of the disease.…”
mentioning
confidence: 99%
“…Because an optimal therapeutic intervention would target early stages of disease, there is a great need for safe and effective ways to detect AMD early and safely monitor its progression. Decline in visual functions, particularly dark adaptation, becomes yet another potential biomarker in monitoring/predicting pathologies leading to AMD (22)(23)(24). Although development of a large number of animal models has helped to advance our understanding of retinal pathobiology and identify specific genetic factors that contribute to photoreceptor degeneration, inflammation, and the biochemistry of many retinal processes, these models all have limitations (25)(26)(27)(28).…”
mentioning
confidence: 99%